Kemampuan Guru Dalam Berkomunikasi Terhadap Peningkatkan Minat Belajar Siswa di SDIT Ummi Darussalam Bandar Setia - Wahyu Iskandar (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Communication is one of the bases to determine teaching success. Teaching success is described from how well teachers can communicates to their students. The aim of this study to investigate: (1) The teachers' ability to communicate towards the improvement of students' learning interest in SD IT Ummi Darussalam Bandar Setia. (2) The supporting and obstacles factors of communication that teachers have in teaching. This research is a type of qualitative study applying direct observation, in-depth interviews and document analysis of data collection. The results of this study prove that teachers' communication in increasing students' learning interest in Elementary School of IT Ummi Darussalam is not good. That happens because there are obstacles that affect miscommunication between them i.e. the teacher has not been able to manage the classroom and master the teaching well by using Bahasa Indonesia in explaining the lesson inside or outside the classroom, so that it affects students' learning interest in Elementary School of IT Ummi Darussalam